What level do disadvantaged firms weight rivals' profits in relative performance evaluations under quantity competition?. (11th October 2020) - Hamamura, Jumpei
Abstract : In the context of quantity competition in relative performance evaluation, this study explores the weight placed on rivals' profits through two asymmetry cases—the cost difference between firms and the sequential choice of weight placed on their rivals' profits. We identify high‐cost firms in the cost asymmetry, and followers in the sequential case of weight decisions are labeled "disadvantaged" firms. Whereas the classical literature demonstrates that the weight placed on a rival's profit is negative under quantity competition, we provide theoretical evidence that the disadvantaged firm assigns a positive weight to the rival's profit under asymmetric cases.